The Influence of the Implementation of Good Corporate Governance and Company Size on Banking Financial Performance in Indonesia - Poppy Camenia Jamil; Nabila Dwi Naswa Putri (Lembaga Riset dan Inovasi Al-Matani, 2025)
The implementation of Good Corporate Governance (GCG) is an important factor in improving banking financial performance. Effective oversight and ownership structure are believed to influence a company's profitability. Additionally, company size also has the potential to impact financial performance. This study aims to determine the effect of GCG implementation, measured through managerial ownership, institutional ownership, and independent commissioners, as well as company size on banking financial performance in Indonesia, measured using Return on Assets (ROA). This study uses panel data from 63 commercial banks registered with the Financial Services Authority (OJK) during the period 2019–2023, with purposive sampling as the sample selection method. The analysis method used is panel data regression with the help of EViews 12 software. The results show that managerial ownership and the independent board of commissioners do not have a significant effect on ROA. Meanwhile, institutional ownership has a significantly positive effect, and company size has a significantly negative effect on ROA. These findings indicate that oversight from institutional shareholders can improve financial performance, while larger companies tend to have lower profitability.